EMOSIONALITAS TOKOH UTAMA NOVEL PERAHU KERTAS KARYA DEWI LESTARI - Yeki Febrianto; Bakhtaruddin Nasution; Nurizzati Nurizzati (Jurnal Bahasa dan Sastra, 2014)
Research aims to describe the main character in the novel Perahu Kertas novel written by Dewi Lestari. This research focused on emotional froms the main character in the novel Perahu Kertas. This research is descriptive qualitative research methods, technical contenyt analysis. The data of this research is the kinds of emotions the main character’s Perahu Kertas novel by Dewi Lestari which includes trace elements based characterzations. The data source of this research is Perahu Kertas novel written by Dewi Lestari published by Bentang Pustaka in 2012. Based on the findings and discussion can be summed up in the Perahu Kertas novel written Dewi Lestari, there are seven main characters of emotions consisting of positive emotions: the sense of comfort, contentment, joy, happines, and a sense of comfort which is compossed of the negative emotions anger and sadness.